The utility of ICD9-CM codes in identifying induction of labor - Levine, Lisa D. (Am J Perinatol, 2014)
BACKGROUND: Data evaluating the accuracy of ICD9-CM codes in identifying inductions are limited. Our objective was to examine the test characteristics of ICD9-CM coding for induction of labor and to identify differences between those captured by coding and those not. METHODS: We performed a retrospective cohort study of ICD9-CM codes in identifying charts of induced women at our institution from 2005-2009. Review of the medical record was the gold standard. Characteristics of the charts were compared using Mann-Whitney U tests and chi-square tests where appropriate. RESULTS: 3263 women were included, 708 with ICD9-CM coding for induction (screen positive). 422 women were randomly sampled from those not coded as induction (screen negative). The sensitivity of ICD9-CM coding for induction was 51.4%, specificity 98.8%, PPV 96.6%, NPV 74.7%. False negative charts (25%) were more likely to be women induced for premature rupture of membranes (40% vs. 8%, p<0.001) or with oxytocin (51% vs. 33%, p<0.001) when compared to screen positive charts. CONCLUSIONS: It is reassuring that 97% of charts coded for induction by ICD9-CM codes are, in fact, patients that were induced. With this degree of accuracy, we can be confident that charts coded as induction are unlikely to be miscoded.